ASEAN economic community and the regional automotive industry: impact of ASEAN economic integration on two types of automotive production in Southeast Asia. (2015) - Kobayashi, Hideo; Jin, Yingshan; Schroeder, Martin
This paper investigates the impact of the on-going economic integration in the ASEAN region on the regional automotive industry. Investigation is not limited to global automotive original equipment manufacturers (OEMs), but includes local assemblers. While ASEAN has implemented policies that promoted the creation of supply chains between member states to further economic development, it will be highlighted how the forthcoming deeper integration policy dubbed ASEAN Economic Community (AEC) 2015 is already influencing industry development. The question is if the politically induced economic integration in ASEAN and industrial policies of individual member states are going to lead to envisioned development of the automotive industry or if this development may be confined to established producing countries. Specifically, the question will be traced if production in all countries is going to develop towards fully integrated production or if companies are going to practice minimal localisation in peripheral markets such as the so-called CLMV countries (Cambodia, Laos, Myanmar, and Vietnam), so that these countries get locked in production that is basically assembly of imported components or manufacturing of intermediate and labour-intensive components.